2019
DOI: 10.1136/tsaco-2018-000263
|View full text |Cite
|
Sign up to set email alerts
|

World trauma education: hemorrhage control training for healthcare providers in India

Abstract: BackgroundHemorrhage remains a major cause of death around the world. Eighty percent of trauma patients in India do not receive medical care within the first hour. The etiology of these poor outcomes is multifactorial. We describe findings from the first Stop the Bleed (StB) course recently offered to a group of medical providers in southern India.MethodsA cross-sectional survey of 101 participants who attended StB trainings in India was performed. Pre-training and post-training questionnaires were collected f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…The ACS certified BCon program has trained over 1 million people in 71 countries worldwide to date 6 . Several studies have reported the efficacy of the BCon course in the USA 9,10 and other countries 9,11–13 . In Spain, it was reported that the BCon course was evaluated as good for relevance, usefulness, applicability, and satisfaction by most of the studied population 13 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ACS certified BCon program has trained over 1 million people in 71 countries worldwide to date 6 . Several studies have reported the efficacy of the BCon course in the USA 9,10 and other countries 9,11–13 . In Spain, it was reported that the BCon course was evaluated as good for relevance, usefulness, applicability, and satisfaction by most of the studied population 13 .…”
Section: Discussionmentioning
confidence: 99%
“…6 Several studies have reported the efficacy of the BCon course in the USA 9,10 and other countries. 9,[11][12][13] In Spain, it was reported that the BCon course was evaluated as good for relevance, usefulness, applicability, and satisfaction by most of the studied population. 13 In India, the vast majority of participants said that they had a high degree of confidence in their wound packing and tourniquet skills.…”
Section: Discussionmentioning
confidence: 99%
“…There have been a few studies in India which analyzed the need for the stop the bleed training in trauma. These studies reported the necessity for training adult responders in bleeding control [10] [11] [12]. In a rural south Indian district, 81.4% of survey respondents did not have adequate skills to manage an emergency before training, but were willing to acquire knowledge and skills to help victims [10].…”
Section: Introductionmentioning
confidence: 99%
“…In a rural south Indian district, 81.4% of survey respondents did not have adequate skills to manage an emergency before training, but were willing to acquire knowledge and skills to help victims [10]. Stop the bleed training for adult healthcare providers (resident and attending physicians and nurses) showed encouraging results where 95% showed improved confidence and competence after the training, including wound packing and tourniquet application [11].…”
Section: Introductionmentioning
confidence: 99%